2020
DOI: 10.1149/1945-7111/abbce1
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Identifying and Managing Reversible Capacity Losses that Falsify Cycle Ageing Tests of Lithium-Ion Cells

Abstract: We report on a cycle ageing study of commercial NCA/Gr+Si cells, in which reversible capacity fluctuations turn a central experimental finding upside down: an upper voltage limit of 4.1 V seems to cause faster degradation than going all the way to 4.2 V. The underlying effect is the reversible loss of lithium inventory into passive anode overhang areas. We demonstrate how the resulting artefact arises from a combination of slow transport processes and the related time periods spent in specific state-of-charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…DVA tracking of cell degradation [16,28,29,44] as illustrated in Figure 9 relies on the DVA markers Q1 to Q5 (all expressed in Ah values) as summarized in Table 3. The left side (Figures 9a, c, e) shows voltage profiles and DVA plots for a cell aged at 0 % SoC and 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…DVA tracking of cell degradation [16,28,29,44] as illustrated in Figure 9 relies on the DVA markers Q1 to Q5 (all expressed in Ah values) as summarized in Table 3. The left side (Figures 9a, c, e) shows voltage profiles and DVA plots for a cell aged at 0 % SoC and 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The cell examined in the present study was found to have an anode area ≈ 790 cm 2 and cathode area ≈ 740 cm 2 , resulting in an overhang ≈ 6%. The resulting non-uniform lithium distribution in the anode material could lead to higher lithium disorder and hence a greater entropy change due to disordered Stage II configurations [59,60,25]; anode overhang areas can also lead to reversible LLI [61]. The net result of all of these effects may lead to some disparities between combined entropy from half-cells and the full-cell entropy change, particularly at the boundaries between graphite phase transitions.…”
Section: Half-cell Entropy Contributionsmentioning
confidence: 99%
“…This resulted in calendar aged cells experiencing a recovery in LLI together with a less pronounced increase in LAM NE . This suggests recovery of capacity from the 'anode overhang' effect [61]. Geometrically, anode overhang is defined as an additional anode area which is not directly opposed by the cathode [76].…”
Section: Impact Of Silicon On Entropy Profilesmentioning
confidence: 99%
“…In this way, anodetocathode ratios in commercial cells are always larger than 1. The anode region which has no cathode counterpart is often called overhang area, and lithium movement from/to these regions are known to cause reversible capacity effects taking place at varied timescales [36].…”
Section: Geometric Parameters and Physical Characterisationmentioning
confidence: 99%